2013
DOI: 10.1098/rspb.2013.1887
|View full text |Cite
|
Sign up to set email alerts
|

Global warming triggers the loss of a key Arctic refugium

Abstract: We document the rapid transformation of one of the Earth's last remaining Arctic refugia, a change that is being driven by global warming. In stark contrast to the amplified warming observed throughout much of the Arctic, the Hudson Bay Lowlands (HBL) of subarctic Canada has maintained cool temperatures, largely due to the counteracting effects of persistent sea ice. However, since the mid-1990s, climate of the HBL has passed a tipping point, the pace and magnitude of which is exceptional even by Arctic standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 53 publications
5
51
1
Order By: Relevance
“…Although this species shift is of interest, by far the more ecologically significant change is the aforementioned increase in planktonic taxa at 12 cm depth as this marks a change in both habitat and life strategy. This broad pattern of abrupt increases in D. stelligera and pennate planktonics within the last 100 years has been documented in hundreds of lakes from alpine, Arctic and temperate regions throughout Europe and North America (Rühland et al, 2013(Rühland et al, , 2015.…”
Section: Diatomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this species shift is of interest, by far the more ecologically significant change is the aforementioned increase in planktonic taxa at 12 cm depth as this marks a change in both habitat and life strategy. This broad pattern of abrupt increases in D. stelligera and pennate planktonics within the last 100 years has been documented in hundreds of lakes from alpine, Arctic and temperate regions throughout Europe and North America (Rühland et al, 2013(Rühland et al, , 2015.…”
Section: Diatomsmentioning
confidence: 99%
“…Often the response to temperature is indirect and caused by fundamental changes to limnological variables such as thermal stability and stratification, habitat alteration, and the availability of light and nutrient resources (Rühland et al, 2015). Nonetheless, when long-term meteorological data are available to compare with paleolimnological data, the timing of biotic assemblage shifts often corresponds with the onset of temperature increases (Michelutti et al, 2015b;Rühland et al, 2013;Antoniades et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They report early signs of a biological response to warming, but note that the magnitude of change varies across sites and trophic levels. Thus, despite evidence of a coherent tem-poral response among primary producers (diatoms) in at least four lakes examined in detail (Rühland et al, 2013), regional stressors may be regulated by local factors (e.g. lake depth, distance to salt water, nutrient status) that moderate the degree of biological response observed.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a high-resolution paleolimnological study of four lakes near the Sutton River in the HBL, Rühland et al (2013) observed biological changes that were regionally coherent and coincident with rapidly warming air temperatures since the early 1990s. Using multiple paleoecological indicators, Rühland et al (2014) provide additional evidence for biological change in HBL lakes.…”
Section: Introductionmentioning
confidence: 99%
“…Climate warming will be most pronounced in northern areas of the province (Colombo et al, 2007), and recent paleolimnological studies of diatoms (Rühland et al, 2013 and cladocerans (Jeziorski et al, 2015) indicate that warming-related community changes are already happening in northern Ontario lakes. As well, future largescale mining activity and associated infrastructure development is inevitable for northern Ontario, with the discovery of massive metal deposits in the 'Ring of Fire' (ROF) area (Hjartarson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%